Should Lutetium-prostate specific membrane antigen radioligand therapy for metastatic prostate cancer be used earlier in men with lymph node only metastatic prostate cancer? - William John Yaxley (Korean Urological Association, 2021)
Purpose: Lutetium labelled prostate-specific membrane antigen radioligand therapy (Lu-PSMA RLT) has shown pleasing early results in management of high-volume metastatic castration resistant prostate cancer (mCRPC), but its role in the early treatment of men with only lymph node metastasis (LNM) is unknown. The aim was to assess the outcome of Lu-PSMA RLT earlier in the treatment of men with only LNM. Materials and Methods: Single institution retrospective review of men with only LNM on staging Ga-PSMA PET PSMA who proceeded with Lu-PSMA RLT. Results: There were 17 men with only LNM, including 13 with mCRPC and 3 who were both hormone and chemotherapy naïve. The median PSA was 3.7 (0.46–120 ng/mL). A PSA decline of ≥50% occurred in 10/17 (58.8%), decreasing to <0.2 ng/mL in 35.3% (6/17). The PSA continues to decline or remain stable in 10/17 (58.8%) with a median follow-up of 13 months, and 8/17 (47.1%) have not reached their pre-treatment levels. There were no significant side effects. There was a better PSA response in men without prior chemotherapy (p=0.05). The prostate cancer specific and overall survival is 82.4% (14/17). Conclusions: Our results identify improved PSA response to Lu-PSMA RLT in men with only LNM, especially in the chemotherapy naïve cohort, compared to previous series with more advanced mCRPC. These findings provide important proof of principle to aid with planning of future prospective randomized trials evaluating the role of Lu-PSMA RLT earlier in the management of node metastatic prostate cancer, including men naïve of ADT and chemotherapy.